2011
DOI: 10.1002/pbc.23072
|View full text |Cite
|
Sign up to set email alerts
|

The time to diagnosis in childhood lymphomas and other solid tumors

Abstract: The TD for childhood lymphomas and solid tumors was related to patient age, tumor type and location, the presence of distance metastases, first health professional, and center contacted. All physicians, especially other specialists seeing pediatric patients, need to be further sensitized to the signs and symptoms of childhood cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 36 publications
9
40
2
Order By: Relevance
“…The differences between the studies may be explained by the country and time period in which the studies were conducted. A study from western Turkey reported parental delay, physician delay and total delay as 3, 28, and 53 days, respectively [9]. In that study, physician delay and total delay were similar to those of our study, whereas parental delay was shorter.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The differences between the studies may be explained by the country and time period in which the studies were conducted. A study from western Turkey reported parental delay, physician delay and total delay as 3, 28, and 53 days, respectively [9]. In that study, physician delay and total delay were similar to those of our study, whereas parental delay was shorter.…”
Section: Discussionsupporting
confidence: 89%
“…Early diagnosis is a fundamental goal in oncology, and time to diagnosis is known to be among the important diagnostic factors [1,4,9,11]. In the published data, time to diagnosis has varied widely [1,3,6].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations